Public Private Partnership: Kolaborasi Pemerintah dan Swasta Dalam Pengelolaan Aset Publik di Kota Makassar - Abdul Mahsyar (Centre for Public Policy and Management Studies, 2015)
This study aims to describe the model of cooperation between the Government of Makassar as the bureaucracy with the private sector within the framework of collaborative governance, and see the effectiveness of such cooperation for the public interest. The study used a qualitative approach, the locus of the two institutions namely Makassar City Government and PT. Tosan Permai as the developer. The focus of research is on the management aspects Karebosi Field. Sources of data obtained from cooperating agencies and also from other stakeholders which are the Land Board, Member of Parliament, and the public of Makassar. Data collected through in-depth interviews, observation, and documentation. Data were analyzed by descriptive qualitative perform data reduction, presentation, interpretation and subsequent inference.The results shows that Makassar City Government handed over the management of public assets to the private sector due to limited resources such as the management of construction and maintenance funds, facilities and personnel. With the cooperation between the private sector collaborative, public asset development can be done quickly and minimize the use of local government budgets. Public asset management right field Karebosi conducted by the Mayor of Makassar with the private sector using the model of contracting out in the form of joint use of the system through the model BGS (Guna Bangun Serah). Within this cooperation mode, each party has the rights and obligations set out in the contract. The results of the collaboration have a positive impact for both sides namely to municipalities to generate revenue (PAD) and no longer burdened with the cost of management and maintenance of land, availability of comfortable public space area and a green area in the city center. Private parties gain the utilization of land and underground around the field as the business district. The society benefits from the availability of public space as a mean of recreations, sports, and other various events.